1994
DOI: 10.1021/ac00086a008
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrin Derivatives as Neutral Carriers for PVC Membrane Electrodes

Abstract: The anion-sensitive membrane electrodes based on lipophilic metalloporphyrin derivatives (FeTPP)20 show similar anti-Hofmeister selectivity sequence: SCN-> I-> C104-> N02-> B r > C1-> NOj-. The electrode with an optimum membrane composition has a linear response for SCN-between and 10-l mol/L, with a slope of 53.0 mV/pSCN-(25 "C). The origin of the anti-Hofmeister response characteristics has been discussed in view of the coordination chemistry of the metalloporphyrins. The interaction mechanism between (FeTPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 25 publications
3
65
0
Order By: Relevance
“…20 20 It can be seen from Tables 4 and 5 that the results obtained by the electrode are coincident with that of HPLC, and that the electrode can be successfully applied to the practical detection of thiocyanate.…”
Section: Preliminary Applicationmentioning
confidence: 69%
See 1 more Smart Citation
“…20 20 It can be seen from Tables 4 and 5 that the results obtained by the electrode are coincident with that of HPLC, and that the electrode can be successfully applied to the practical detection of thiocyanate.…”
Section: Preliminary Applicationmentioning
confidence: 69%
“…Electrodes based on porphyrin and vitamin B12 derivatives, reported previously, also showed a similar effect of OH -on the potentiometric response. 16 BNSDM, and the selectivity coefficients were compared with that of an electrode containing a quaternary ammonium salt, hexadecyltrioctylammonium iodide (HTOAI) 19 and an electrode based on bis-bebzoin-semitriethylenetetraamine binuclear copper(II) (Cu(II)2-BBSTA) 10 and metal(III) porphyrin ionophores 20 (see Table 2). From the table, we can see that the electrode containing Cu(II)-BNSDM showed a higher selectivity than that mentioned in the literature and displayed an anti-Hofmeister selectivity sequence: thiocyanate > perchlorate > iodide > salicylate > bromide > nitrite > chloride > nitrate > phosphate > sulfate.…”
Section: Potentiometric Response Characteristics Of Electrodesmentioning
confidence: 99%
“…[20][21][22][23] Gao et al reported an μ-oxo-bis-tetraphenyl-porphinatomanganese(III) based electrode showing potentiometic response to SCN -with an anti-Holfmeister selectivity pattern as SCN -> ClO4 -> I -> NO2 -> NO3 -> Br -> Cl -. 24 Inspired by the successful work of Gupta and Gao, in the context of our long-term interests in searching for novel porphyrin derivatives as carriers for sensors, 22,23,[25][26][27][28] we have tried to investigate the μ-oxo-bridged metalloporphyrin dimers as carriers to see whether the response characteristics of the electrode could further be improved. This paper describes the use of several metalloporphyrin complexes as electroactive materials for the preparation of molybdate-sensitive electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Among different anion carriers used for this purpose, 4 the use of metalloporphyrins, [5][6][7][8][9][10] metal complexes, 11,12 and organometalic compounds 13,14 as ionophores in solvent polymeric membrane electrodes are well known to induce potentiometric anion selectivity sequences that differ significantly from the classical Hofmeister pattern. [5][6][7][8][9][10][11][12][13][14] Despite the need for a triiodide ion-selective electrode for the determination of iodide and triiodide ion in many medical, 17,18 juice (as ascorbic acid in orange juice) 20 and environmental samples (such as dissolved O2 in water), [15][16][17][18][19][20][21][22][23] to date there have been limited reports on an I3 -ion-selective electrode in the literature. [17][18][19]22,23 Furthermore, it is interesting to note that, to the best of our knowledge, there is one literature report concerning the use of charge-transfer complexes of crown ethers for preparing an ion-selective electrode.…”
Section: Introductionmentioning
confidence: 99%